Mathematical modeling of the mechanical characteristic of the activated PTFE-matrix using the method of planning the experiment - Bilous O. A.; Hovorun T. P.; Berladir K. V.; Vorobiov S. I.; Simkulet V. V. (Журнал інженерних наук)
In this paper, the influence of the parameters of the technological process of mechanical activation on the physical characteristics of the polytetrafluoroethylene (PTFE) matrix is investigated. The paper presents a mathematical model of the dependence of breaking strength on the time of activation and rotating speed of working organs of a mill. Mathematical modeling is performed by the method of orthogonal experiment planning. The result of the study was a mathematical relation that explains the connection between the technical characteristics of the process of manufacturing a fluoroplastic composite and the mechanical characteristics of the material. The statistical analysis of the experimental results is performed and the adequacy of the mathematical relations obtained is estimated. On the basis of the analysis of the obtained data, it can be concluded that the theoretical model obtained is adequate and suitable for performing the corresponding technological calculations. On the basis of the performed calculations, the conclusion is reached on the optimal technological mode of preparing the PTFE-matrix. The analysis shows that theoretical calculations confirm the experimental value of technological indicators under optimal operating conditions of the mill. Thus, the obtained dependence of breaking strength from the technological parameters of the activation process can be embedded in the algorithm for selecting the technological mode that ensures the output of products with specified quality indicators.